2015
DOI: 10.1016/j.freeradbiomed.2014.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Posttranslational modification of Sirt6 activity by peroxynitrite

Abstract: The mammalian sirtuin 6 (Sirt6) is a site-specific histone deacetylase that regulates chromatin structure and many fundamental biological processes. It inhibits endothelial cell senescence and inflammation, prevents development of cardiac hypertrophy and heart failure, modulates glucose metabolism, and represses tumor growth. The basic molecular mechanisms underlying regulation of Sirt6 enzymatic function are largely unknown. Here we hypothesized that Sirt6 function can be regulated via posttranslational modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 51 publications
0
34
0
Order By: Relevance
“…It has been hypothesized that, under oxidative and nitrosative stress, SIRT6 activity can be regulated via reactive nitrogen species-mediated posttranslational modifications (71). Indeed, incubation of purified recombinant SIRT6 protein with 3-morpholinosydnonimine, a donor of peroxynitrite, increased nitration at tyrosine 257 and decreased the catalytic activity (71).…”
Section: Redox Regulation Of Sirt6 In Vascular Protectionmentioning
confidence: 99%
“…It has been hypothesized that, under oxidative and nitrosative stress, SIRT6 activity can be regulated via reactive nitrogen species-mediated posttranslational modifications (71). Indeed, incubation of purified recombinant SIRT6 protein with 3-morpholinosydnonimine, a donor of peroxynitrite, increased nitration at tyrosine 257 and decreased the catalytic activity (71).…”
Section: Redox Regulation Of Sirt6 In Vascular Protectionmentioning
confidence: 99%
“…In addition, significantly increased SIRT6 nitration and decreased deacetylase activity of SIRT6 were also found in an endotoxin-induced retinal inflammation mice model, indicating that SIRT6 nitration is correlated to retinal inflammation. In summary, tyrosine nitration may act as a novel regulatory mechanism to negatively control SIRT6 activity (Hu et al 2015).…”
Section: Nitrationmentioning
confidence: 99%
“…Protein tyrosine nitration is a kind of posttranslational modification when tissues under nitrative stress. It was reported that nitration of mitochondrial proteins led to their inactivation and mitochondrial dysfunction[44], and a recent report revealed that nitration of Y257 in sirtuin 6 inhibited its function [45]. Nitration of TIM at Y165 and Y209 has been demonstrated to induce a decrease in its activity [46].…”
Section: Discussionmentioning
confidence: 99%